Measuring Community Strengths – Using Data from The First Nations Regional Health Survey Linked with A Whole-Population Administrative Data Repository - Nickel, Nathan C; Phillips-Beck, Wanda; Campbell, Rhonda; Chateau, Dan; Sarkar, Joykrishna; Chartier, Mariette; Enns, Jennifer; Burland, Elaine; Quddus, Farzana; Brownell, Marni (International Journal of Population Data Science, 2020)
Introduction Administrative data studies routinely report that First Nations mothers and children experience a disproportionate burden of poor health. Due to the nature of administrative data, research often takes a deficits-oriented approach. First Nations health research needs to consider the role that community- and individual-level strengths play in promoting wellbeing and examine how these interact with the delivery and outcomes of health programs. Objectives and Approach The First Nations Health and Social Secretariat of Manitoba (FNHSSM) and the University of Manitoba partnered to construct measures of community-level strengths that can be linked with administrative data to examine the delivery and outcomes associated with population health programs delivered in First Nations communities. We linked data from the FNHSSM-administered Regional Health Survey (RHS) with administrative data housed in the Manitoba Population Research Data Repository. We identified 60 questions from the child, youth, and adult versions of the RHS to measure community strengths. We used principal component analysis to identify strength-based constructs. We used Eigen values and percent of variance explained to determine the final number of factors. We used random group resampling and bootstrap methods to test for community-level homogeneity. Community-level factor scores were calculated as the scaled combination of RHS questions within each factor and averaged to the community. Results We identified 12 constructs of community strength: 5 from child responses, 4 from youth, and 3 from adult responses. Strength-based constructs common to all age groups included knowledge of traditional language, involvement in cultural events, and connection with community. Conclusion / Implications Colonial approaches to health research perpetuate deficit-based dialogues and negative portrayal of First Nations peoples. First Nations health research should consider how community strengths promote health and interact with program delivery. Including measures of community strength leads to richer understandings of factors that promote wellness among First Nations peoples.